Practical training at Perpustakaan Tun Abdul Razak 1 UiTM Shah Alam, Malaysia / Muhammad Fadzli Ramly - Ramly, Muhammad Fadzli (2008)
The library was first set up in 1960 under the Rural and Industrial Development Authority (AIDA) in Petaling Jaya. In 1972 a new main library building was completed in Shah Alam and named Perpustakaan Tun Abdul Razak 1. To date the library collections totaled more than 600,500 volumes comprising books, pamphlets, conference papers, bibliographies, calendars and other non-print materials in microform format. The library also holds about 5,000 periodical titles currently subscribed or received through request/donations. A number of 53 online databases are subscribed from various journals.